An audit of process and outcome for emergency colectomy in England and Wales. (3rd October 2020) - Burns, E. M.; Poulton, T.; Deputy, M.; Pinkney, T.; Guy, R.
Abstract: Aim: The aim of this work was to describe process and outcome for patients undergoing emergency colectomy for colitis in England and Wales. Method: The National Emergency Laparotomy Audit (NELA) is a national audit including patients undergoing emergency laparotomy and laparoscopic resectional procedures. Data from adult patients under 65 years of age who underwent emergency subtotal colectomy or panproctocolectomy for colitis between 2013 and 2016 were analysed. Results: In total 1204 patients were included. Although approximately a third of patients underwent a colectomy within 5 days of admission [37% (440/1204)], 32% (383/1204) were admitted for more than 10 days prior to surgery. Colorectal surgeons were present at operation in 72% (869/1204) of cases and consultant surgeons attended 94% (1137/1204) of procedures. Laparoscopy was attempted in 32% (390/1204) of operations with wide institutional variation in its use (0–100% of cases). The overall 30‐day inpatient mortality was 2.9% (35/1204). On multivariable regression analysis, age > 55 years [OR 3.59 (1.05–12.21), P = 0.041], female gender [OR 2.88 (1.27–6.52), P = 0.011] and American Society of Anesthesiologists grade 5 [OR 37.43 (2.72–514.52), P = 0.007] were associated with increased mortality. Conclusion: There is a consultant‐driven service that is largely delivered by specialist colorectal surgeons. Laparoscopy rates were high although there was wide variation in use across institutions. Preoperative delays were evident, and further work is necessary to determine the underlying reasons for these.